EKSPRESI RASA DALAM KARYA LUKIS - Muhammad Arifin, Drs. Abd. Hafiz, M.Pd, Yasrul Sami, S.Sn., M.Sn. (Universitas Negeri Padang, 2016)
The purpose in making this thesis is to create paintings that reveal the expression of the expressive technique on canvas. The methods in the process of making this work is done through the realization of the ideas of art with several steps: Preparation, inspiration, incubation, elaboration. These works are created through various processes and experiences in the life of the author himself as for the work that the author created was titled: “Taste In The Art of Expression”.Keywords: Expression, Paintings, Expressive